Identifikasi Sektor Unggulan Kabupaten Lamongan: Tahun 2006 2010 - Siti Fatimah Nurhayati; Eny Kusumawati (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractDevelopment focus was more on macroeconomic growth during New Order era. Consequently, a significant development inequality occurred among regions with a potential conflict. Considering the problem, central government enacted local autonomy policy in 1999 and revised by Act No. 32 of 2004. The policy is expected to make local governments being able to organize discretionally more effective and efficient local developments. It is also expected to occur in Lamongan Regency. The research aims to identify leading sectors and to analyze change pattern of economic structure of Lamongan Regency of 2006-2010.Shift Share’s Esteban Marquilas is used to identify the leading sectors and pattern of economic structure change can be known from this. The results indicated farming and services as the leading sector. Economy of Lamongan is in transition dominated by primer to secondary and tertiary sectors